A comparison of the structures of some 2- and 3-substituted chromone derivatives: a structural study on the importance of the secondary carboxamide backbone for the inhibitory activity of MAO-B - Gomes, Ligia R. (2015)
The crystal structures of the 3-substituted tertiary chromone carboxamide derivative, C17H13NO3, N-methyl-4-oxo-N-phenyl-4H-chromene-3-carboxamide (1), and the chromone carbonyl pyrrolidine derivatives, C14H13NO3, 3-(pyrrolidine-1-carbonyl)-4H-chromen-4-one (3) and 2-(pyrrolidine-1-carbonyl)-4H-chromen-4-one (4) have been determined. Their structural features are discussed and compared with similar compounds namely with respect to their MAO-B inhibitory activities. The chromone carboxamide presents a -syn conformation with the aromatic rings twisted with respect to each other [the dihedral angle between the mean planes of the chromone system and the exocyclic phenyl ring is 58.48 (8)°]. The pyrrolidine derivatives also display a significant twist: the dihedral angles between the chromone system and the best plane formed by the pyrrolidine atoms are 48.9 (2) and 23.97 (12)° in (3) and (4), respectively. Compound (3) shows a short C-H...O intramolecular contact forming an S(7) ring. The supramolecular structures for each compound are defined by weak C-H...O hydrogen bonds, which link the molecules into chains and sheets. The Cambridge Structural Database gave 45 hits for compounds with a pyrrolidinecarbonyl group. A simple statistical analysis of their geometric parameters is made in order to compare them with those of the molecules determined in the present work.